Individualized small bowel preparation for computed tomography enterography: A prospective randomized controlled trial - Sun, Yi‐Ning; Li, Yue‐Yue; Zheng, Meng‐Qi; Liang, Yong‐Feng; Ji, Rui; Yang, Xiao‐Xiao; Qu, Jun‐Yan; Li, Zhen; Zuo, Xiu‐Li; Li, Yan‐Qing (Journal of gastroenterology and hepatology, 2024)
Background and Aim The study aims to evaluate the feasibility of body mass index (BMI)‐based individualized small bowel preparation for computed tomography enterography (CTE). Methods In this prospective randomized controlled study, patients undergoing CTE were randomly assigned to the individualized group or standardized group. Those in individualized group were given different volumes of mannitol solution based on BMI (1000 mL for patients with BMI < 18.5 kg/m2, 1500 mL for patients with 18.5 kg/m2 ≤ BMI < 25 kg/m2 and 2000 mL for patients with BMI ≥ 25 kg/m2) while patients in the standardized group were all asked to consume 1500‐mL mannitol solution. CTE images were reviewed by two experienced radiologists blindly. Each segment of the small bowel was assessed for small bowel image quality and disease detection rates. Patients were invited to record a diary regarding adverse events and acceptance. Results A total of 203 patients were enrolled and randomly divided into two groups. For patients with BMI < 18.5 kg/m2, 1000‐mL mannitol solution permitted a significantly lower rate of flatulence (P = 0.045) and defecating frequency (P = 0.011) as well as higher acceptance score (P = 0.015), but did not affect bowel image quality and diseases detection compared with conventional dosage. For patients with BMI ≥ 25 kg/m2, 2000‐mL mannitol solution provided better overall image quality (P = 0.033) but comparable rates of adverse events and patients' acceptance compared with conventional dosage. Conclusions Individualized bowel preparation could achieve both satisfactory image quality and patients' acceptance thus might be an acceptable alternative in CTE.